Pelatihan Penulisan Notasi Balok melalui Penciptaan Lagu Anak pada Guru TK Se-Kecamatan Tandes Surabaya - Marda Putra Mahendra; Dhani Kristiandri; Vivi Ervina Dewi; Agus Suwahyono; Moh. Sarjoko (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2025)
The role of teachers in learning music is very important to the development of children, especially in Early Childhood Education (PAUD). Education unit data of Tandes Surabaya sub-district has 116 schools that focus on Early Childhood Education (PAUD). In general, kindergarten teachers in the Tandes Surabaya area in the learning process use the learning model of listening and imitating videos on Youtube. This is a problem for kindergarten teachers in the Tandes Surabaya sub-district area. Kindergarten teachers in the Tandes Surabaya area should have competence in reading notation, writing notation, and making songs, especially children's songs. The purpose of the training on writing beam notation through the creation of children's songs for kindergarten teachers in Tandes Subdistrict is to improve teachers' competence in reading beam notation, writing beam notation and creating simple children's songs. This training was conducted in May-August 2024 through 4 stages, namely 1) Preliminary study and target audience; 2) Preparation of materials and small-scale trials; 3) Determination of activity schedule; 4) Activity implementation and; 4) Activity evaluation. The training participants were 53 kindergarten teachers in Tandes Sub-district, Surabaya. The results of this training are 5 children's songs created by kindergarten teachers in Tandes Surabaya District which are equipped with music notation and get Intellectual Property Rights (IPR).Keywords; community service; community; music; notation; song